2023
DOI: 10.3390/antibiotics12101559
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Escherichia coli Isolated from Dairy Animals Identifies Virulence Factors and Genes Enriched in Multidrug-Resistant Strains

Bradd J. Haley,
Seon Woo Kim,
Serajus Salaheen
et al.

Abstract: The gastrointestinal tracts of dairy calves and cows are reservoirs of antimicrobial-resistant bacteria (ARB), which are present regardless of previous antimicrobial therapy. Young calves harbor a greater abundance of resistant bacteria than older cows, but the factors driving this high abundance are unknown. Here, we aimed to fully characterize the genomes of multidrug-resistant (MDR) and antimicrobial-susceptible Escherichia coli strains isolated from pre-weaned calves, post-weaned calves, dry cows, and lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Dairy calves are often born anemic and for the first eight weeks of life are predominantly fed a milk/milk-replacer diet, which is low in iron compared to the forages of older post-weaned animals [ 32 ]. We have previously hypothesized that this low-iron environment selects for strains that encode accessory siderophores, such as those strains with iucABCD-iutA and sitABCD [ 11 , 12 ]. These two iron-scavenging operons are frequently located on an IncFIB plasmid that can simultaneously encodes ARGs [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Dairy calves are often born anemic and for the first eight weeks of life are predominantly fed a milk/milk-replacer diet, which is low in iron compared to the forages of older post-weaned animals [ 32 ]. We have previously hypothesized that this low-iron environment selects for strains that encode accessory siderophores, such as those strains with iucABCD-iutA and sitABCD [ 11 , 12 ]. These two iron-scavenging operons are frequently located on an IncFIB plasmid that can simultaneously encodes ARGs [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug-resistant E. coli ST117 can be found in the bovine calf gut, which is an iron-poor environment because of the low iron levels in colostrum and milk [11,12,29]. Previous research has identified a positive association between the presence of iron-scavenging genes and the MDR genotype in E. coli collected from young calves [11,12].…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations